Characterization of duck germplasm of eastern hill and plateau region of Jharkhand - KAMAL, REENA; CHANDRAN, P C; DEY, AMITAVA; TANTIA, M S; RAY, P K; KUMARI, R; SARMA, KAMAL (The Indian Journal of Animal Sciences, 2022)
Information about phenotypic characteristics is a basic need in animal genetic resource conservation and improvement. Phenotypic characteristics of Jharkhand ducks from six districts (Palamu, Gadhwa, Latehar, Lohardaga, Khuti, and Simdega) were studied. Data on morphological and morphometric traits were analyzed. The results revealed that the predominant plumage colours of the head, neck, breast, wings and tails were black (56.25%) in drake, and black and white mix (65.33%) in duck; white and black/brown mix (62.50%) in drake, and white (79.33%) in duck; brown (41.25%) in drake, and white and black/brown mix (52.67%) in duck; black/brown and white mix (43.75%) in drake and duck (74.67%); black in drake (75%) and duck (90%) respectively. The dominant bill colour in drake was greenish black (56.25%) followed by orange (25%) and duck bill colour was black (58.67%) followed by orange (22%), whereas dominant eye colour was brown in both the sexes. The predominant shank and web colour were orange (65.0%) in drake and duck (68.0%) respectively. The Jharkhand ducks are unique in their morphological features with attractive black and white plumage colour pattern. The ducks are well acclimatised to local agro-climatic conditions with less input from duck farmers. The hatching and brooding process are natural. The average egg production was 66.92±2.00 eggs. The average adult body weights of drake and ducks were 1.64±23.19 and 1.51±30.09 kg, respectively. Variations were observed in qualitative traits. The observed phenotypic diversity in Jharkhand local ducks could be useful in designing breeding programs and selection.